2017
DOI: 10.2139/ssrn.3060837
|View full text |Cite
|
Sign up to set email alerts
|

How Does Human Capital Matter? Evidence from Venture Capital

Abstract: We investigate the effects of human capital mobility on venture capital (VC) investment and outcomes. To establish causality, we use a difference-indifferences approach that relies on plausibly exogenous variations generated by states' staggered recognition of the inevitable disclosure doctrine (IDD). We _find that a reduction in human capital mobility reduces VCs' investment propensity and successful exit. Further analysis shows that the effects are more pronounced in industries with more high-skilled workers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…However, Dey and White (2021) found that in response to IDD adoption, firms increased anti‐takeover provisions when human capital was important. Related to concerns about the flow of employees, Gu, Huang, Mao, and Tian (2020) found that venture capitalists (VCs) are more likely to invest in IDD adoption states in startups with higher human capital, especially when VC investment has higher uncertainty in returns and when monitoring costs are high.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…However, Dey and White (2021) found that in response to IDD adoption, firms increased anti‐takeover provisions when human capital was important. Related to concerns about the flow of employees, Gu, Huang, Mao, and Tian (2020) found that venture capitalists (VCs) are more likely to invest in IDD adoption states in startups with higher human capital, especially when VC investment has higher uncertainty in returns and when monitoring costs are high.…”
Section: Theoretical Backgroundmentioning
confidence: 99%